A Study on the Studentsâ Writing Skill in Procedure Text at the Ninth Grade Students of SMPN 1 Rambah Hilir - Susanti, Elva; Antoni, Rivi; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research purposes to find the studentsâ writing skill at ninth grade students of SMPN 1 Rambah Hilir. This research was descriptive qualitative. The numbers of population were 92 students. It was consists of 4 class, each class was 23 students. To select the sample the researcher used clustering random sampling technique. The researcher took one class as be sample, it was class IX A that consists of 23 students. The data of this research was studentsâ score in writing procedure text. The data was collected by using written test. After that, the researcher analyze the data was helped by 3 raters. The findings of the research show that the studentsâ writing skill in procedure text, was scores 78,82. It means that the studentsâ skill in procedure text was in good category.